Keeping a critical eye on “lexical friends”: cognates as critical pedagogy in pre-service teacher education (2008)
This research project investigates more productive, critical and reflective ways of teaching cognates and loan words. The main objective of the research is aimed at making teacher trainees aware of different ways of presenting and practising cognates and loan words in the second-language classroom. The participants in the investigation were studying in a BA programme in Teaching English as a Foreign Language in a Mexican public university. This study argues that cognates are a productive resource for second-language users at all stages and levels of language learning and are not just a tool for the random recognition of words. Furthermore, I describe activities that offer ways for language learners to take control of language learning and not just rely on given knowledge from teachers and textbooks. Key words: Vocabulary, cognates, loan words, critical pedagogy Este proyecto de investigación tiene como propósito buscar métodos productivos, críticos y reflexivos en la enseñanza de cognados y préstamos léxicos. El objetivo principal consiste en crear maestros más conscientes sobre las diferentes maneras de presentar y practicar los cognados y los préstamos. Los participantes en este estudio están cursando la Licenciatura de la Enseñanza de Inglés como Lengua Extranjera en una universidad pública en México. Este estudio argumenta que los cognados son un recurso productivo para el alumno que estudia en cualquier nivel y no solamente una herramienta aleatoria para reconocer palabras. Detallo actividades que ofrecen diferentes maneras para que los alumnos asuman el control del proceso de aprendizaje y que no dependan solamente de los conocimientos dados por maestros y libros de texto. Palabras clave: Vocabulario, cognados, préstamos y pedagogía crítica